OPSI PILIHAN KESANGGUPAN MEMBAYAR UANG PENGGANTI BAGI TERPIDANA MEMPERSULIT PENGEMBALIAN KERUGIAN KEUANGAN NEGARA - Muhamad Devan Fadillah (2022)
The Corruption Crime is inseparable from the Compensation Money Crime which is part of an additional crime to recover state financial losses. Compensation money In corruption crimes it is often not in accordance with the amount of state financial losses caused by corruption itself due to the many ways that are used by defendants to cover up the proceeds from their corruption. In this thesis, we will discuss the rule of law if the defendant declares his inability to pay replacement money because many of them prefer the subsidiary punishment, namely imprisonment, where the rules regarding replacement money are only contained in Article 18 with the setting based only on " The maximum refund of the same amount as the property obtained from the crime" then in the Asset Confiscation it comes with the NCB (Non Conviction Based) Asset Forfeiture mechanism which contains asset confiscation without punishment contained in Law No. 7 of 2006 concerning ratification of laws Uncac which is contained in article 54 namely the state must be able to take the necessary actions to save assets with an asset confiscation system without punishment. For a theoretical review using the Combined Theory and Dettrence Effect Theory. The results of the research after an analysis of several articles in the law and the draft law so that the right rules are obtained to ensnare the accused in corruption, especially replacement money, and the implementation of the Asset Confiscation Bill in corruption crimes is considered effective in overcoming state financial losses due to corruption crimes